2018
DOI: 10.1016/j.addma.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical composition on microstructure, strength and wear resistance of wire deposited Ni-Cu alloys

Abstract: Two Ni-Cu alloys (Monel K500 and FM 60) having various Mn, Fe, Al, Ti and C contents were deposited on a Monel K500 plate at three different speeds using wire arc additive manufacturing technique. Microstructure characterisation, in particular a detailed study of precipitates, was carried out using optical and scanning electron microscopy. Mechanical properties were assessed using hardness, tensile and wear testing. For similar deposition conditions, Monel K500 has exhibited smaller secondary dendrite arm spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The low wear resistance of titanium alloy is due to its poor abrasion resistance and undefended oxide layer. Therefore, several surface modification methods have been developed to improve the wear resistance of alloys, such as thermal spray coating which can cause distortion and thermal damage to the substrate if not properly controlled [21], and laser cladding coating because laser cladding equipment is relatively expensive and requires a high level of operator training and experience [22], and chemical composition deposition due to the possibility of collapse under applied stress or sliding velocity, the hard coatings placed on the comparatively soft Ti-6Al-7Nb alloy matrix might be very damaging to their joints implant uses [23]. Furthermore, implementation of such surface modification methods remains difficult due to the compatibility and wettability of the coating within the metal matrix.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The low wear resistance of titanium alloy is due to its poor abrasion resistance and undefended oxide layer. Therefore, several surface modification methods have been developed to improve the wear resistance of alloys, such as thermal spray coating which can cause distortion and thermal damage to the substrate if not properly controlled [21], and laser cladding coating because laser cladding equipment is relatively expensive and requires a high level of operator training and experience [22], and chemical composition deposition due to the possibility of collapse under applied stress or sliding velocity, the hard coatings placed on the comparatively soft Ti-6Al-7Nb alloy matrix might be very damaging to their joints implant uses [23]. Furthermore, implementation of such surface modification methods remains difficult due to the compatibility and wettability of the coating within the metal matrix.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Applying wear test to 316L and 420 steels, the wear resistance of specimens dropped in almost half and one third, respectively. The increased resistance against wear can be associated with dominant chemical compounds, such as chromium carbide, iron carbide, nickel chromium, austenitic and martensitic structures, and hardness [37][38][39][40][41][42][43][44]. In the lubricated test condition, lower viscosity (L1) and higher viscosity (L2) lubricants are used, and test results showed that lower viscosity lubricant enabled lower wear rate and higher viscosity lubricant cannot lowered the wear rate.…”
Section: Wear Rate Evaluationsmentioning
confidence: 99%
“…However, the precipitation strengthening capacity in the Ni-Cu alloy system can be improved with appropriate alloying element additions and heat treatment. Ni-Cu alloys are easily weldable [97] and were successfully used as an input material in powder based [98] and wire arc additive manufacturing [99]. Development of these modern technologies allows to apply the Ni-Cu alloys as a surface cladding material for protection of less corrosion resistant core or in components with mechanical properties gradient.…”
Section: Mechanical Propertiesmentioning
confidence: 99%